Usage of echocardiography with physical loads for diagnosis of myocardial contractile reserve of the left ventricle in athletes. - O. B. Nekhanevich; M. A. Kuznetsova (Medičnì Perspektivi, 2014)
The work purpose was studying of myocardial contractile reserve of the left ventricle and cardiohemodynamics infringements character under the influence of physical loads in athletes with functional insufficiency of mitral valve according to stress-echocardiography. We examined 72 athletes the aged 9 to 40 years with functional mitral valve insufficiency and normal systolic function of the heart at rest by echo ECG data. Possibility of stress echocardiography with physical loads usage to diagnose decrease of myocardial contractile reserve of the heart left ventricle was proved. It was found that increase in hemodynamic load during physical exercise leads to the disruption of adaptation and manifestation of systolic dysfunction in athletes with I and II degrees of mitral valve regurgitation. This should be considered when constructing training-competitive loads among athletes in terms of prevention of acute physical overloading.